Four encolpia from a monastery complex in Naqlun — a preliminary iconographic analysis - Agnieszka Ryś (Polish Archaeology in the Mediterranean, 2017)
The article discusses the iconography of the four cross-shaped encolpia made of lead that were discovered in a monastery complex in Naqlun, Egypt, in 2011. The pendants were found together, apparently mislaid in the northeastern corner of the main room of building K.1 (Northern Building). The iconographic analysis of the decorative elements on these encolpia is based on a comparison with other objects of this type coming from a Byzantine culture context. The dating based on the iconographic analysis is compatible with the archaeological context placing the deposition before the end of the 10th century